Obstetric and perinatal outcomes following frozen and fresh embryo transfer in patients with endometrial hyperplasia and carcinoma: a retrospective study in a high-volume reproductive center - Xuan Zong; Yaxing Guo; Hongzhen Li; Rong Li; Jie Qiao (BMC, 2023)
Abstract Background There is ongoing debate regarding which embryo transfer procedure can achieve a higher live birth rate. Research has suggested that frozen ET might be beneficial for certain populations, such as hyper-responders. This study aimed to compare outcomes of pregnancies between frozen and fresh embryo transfer cycles in patients with endometrial hyperplasia and carcinoma. Methods This retrospective cohort study was conducted at a high-volume reproductive center from January 2010 to January 2022. Patients who were diagnosed with endometrial hyperplasia with atypia and endometrial carcinoma were included. They all underwent in vitro fertilization after conservative treatment. The primary outcome was live birth after frozen and fresh embryo transfer cycles, and secondary outcomes included perinatal complications and other pregnancy outcomes. Results Overall, 259 ET cycles (130 fresh and 129 frozen) were included. The rate of live births per embryo transfer cycle of the whole cohort was 20.8% (54/259), and no significant between-group difference was found after adjusting for potential confounding factors (23.8% vs. 17.8%; adjusted OR, 0.47; 95% CI, 0.21-1.06; p=0.068). Compared to fresh embryo transfer group, the incidence of total maternal complications in the frozen embryo transfer group was significantly higher (30.4% vs. 6.5%, p=0.019). Analyzing each complication as a separate entity, patients in the frozen embryo transfer group had a higher incidence of hypertensive disorders of pregnancy (p=0.028). Multiple logistic regression analysis showed that frozen embryo transfer was related with an increased occurrence of maternal complications (OR, 6.68, 95% CI, 1.01-44.19, p=0.040). Conclusions Among patients with endometrial hyperplasia and carcinoma, the rate of live births was comparable between both embryo transfer procedures, while frozen embryo transfer might be associated with a higher risk of maternal complications compared to that with fresh embryo transfer.